Negotiating Religious Identities and Modernity in Maluku: A Socio-Historical Perspective - Gaspersz, Steve Gerardo Christoffel; Souisa, Nancy Novitra (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2023)
This research article was based on a literature review using the lens of a socio-historical perspective on the dynamic relationship between Islam and Christianity in Maluku throughout the social history of the Maluku archipelago. The research question “How did the metamorphosis of religious identities (Islam and Christianity) take place through the history and contemporary social reality in Ambon?” becomes a reference to trace the historical trajectory of relations between the two religions in Maluku. The religious conflict that occurred from 1999-2005 still leaves social residues that must be carefully considered for the future of these two religions in Maluku and Indonesia. A hermeneutic analysis of social history was used to map the sociological variables that determine the existence and interaction of Islam and Christianity in Maluku, which in turn also determine interfaith relations at large in the context of Indonesia’s pluralistic society. A multidisciplinary approach was used to synthesize various documents and analyses of some experts, especially Pierre Bourdieu’s sociological analytical framework. The result of this research is the construction of historical understanding that must be understood in managing religious pluralism, especially in the relations between Islam and Christianity in Maluku and Indonesia.